The role of identity in how whole‐blood donors reflect on and construct their future as a plasma donor. (29th July 2019) - Thorpe, Rachel; Masser, Barbara M.; Jensen, Kyle; Van Dyke, Nina; Davison, Tanya E.
Abstract: In the context of decreased demand for whole blood and increased demand for plasma‐derived products, donors in Australia are increasingly being asked to convert from whole‐blood to plasmapheresis donations. Plasmapheresis is a different type of donation to whole blood as the process takes longer and can be engaged in more frequently. What is unknown is whether whole‐blood donors view donating plasma as consistent with their donor identity and how they respond to the possibility of donating more frequently. To explore this, we undertook semistructured telephone interviews with 26 whole‐blood donors who had recently made their first plasma donation. Findings indicated that whereas donating plasma was viewed as a bigger ask than donating whole blood, the former was viewed as consistent with their identity as a donor because both behaviours were seen to benefit others and self and were located within the same institutional context. Donating plasma was an opportunity for donors to enhance their self‐concept as an altruistic giver. When contemplating their future donation behaviour, donors considered how their donor identity would fit alongside other salient roles. These findings have implications for how institutions can position their request of existing donors to give a different gift.